The Effect of PrimaKu Application Education on Parents' Knowledge in Monitoring Children's Growth and Development in Dete Village, Lape District - Hasifah, Herni; Iga Maliga; Ana Lestari; Rafi’ah, Rafi’ah (Sean Institute, 2025)
The growth and development of Indonesian children still requires serious attention because the rate of growth and developmental delays remains high. About 5-10% of children experience common developmental delays. Two out of 1,000 babies experience motor delays; three to six babies experience developmental delays and hearing problems; and one in 100 children experience intellectual and language delays. This study aimed to determine the effect of the PrimaKu educational application on parents' knowledge of monitoring their children's growth and development. The study employed a quasi-experimental pre-test post-test design with a control group. The study sample consisted of 160 respondents. The results revealed that the average pre-test knowledge score was 2.73, with a standard deviation of 0.571. The average post-test knowledge score was 1.34, with a standard deviation of 0.635. The mean difference between the pre-test and post-test was 1.381, with a standard deviation of 0.734. The statistical test results yielded a p-value of 0.000, indicating a significant difference in respondents' knowledge before and after receiving education. Therefore, it can be concluded that the PrimaKu application education significantly improves mothers' knowledge of monitoring their children's growth and development.